Characterization of a multi-electrode bulk-SOA for low NF in-line amplification in passive optical networks - Bradley, Louise (My University, 2010)
A bulk semiconductor optical amplifier (SOA) utilizing a multi-contact biasing method is characterized as a function of the bias current supplied to each section Firstly, amplified spontaneous emission spectra and characteristic light-current profiles are analyzed. Single-pass gain and noise figure of the SOA are then assessed by injecting a continuous wave input beam. Finally, the amplification of a 10 Gb/s (2 15 -1) long pseudo random bit sequence signal is analysed. The obtained results, particularly at a bias condition of 90mA-50mA-10mA, reveal the potential of this device as a low noise figure in-line amplifier.
12th International Conference on Transparent Optical Networks (ICTON)
PUBLISHED
Keywords: Noise measurement; Passive Optical Networks (PON); Semiconductor optical amplifiers; Spontaneous emission; Optical amplifiers; Noise figure; Optical noise; Fiber nonlinear optics; Current supplies; Stimulated emission